Epidemiological Characteristics and Formation Mechanisms of Multidrug-Resistant Hypervirulent Klebsiella pneumoniae - Tang, Miran; Kong, Xin; Hao, Jingchen; Liu, Jinbo (Frontiers in Microbiology, 2020)
Multi-drug resistance (MDR) and hypervirulence (hv) were exhibited by different well-separated Klebsiella pneumoniae lineages in the past, but their convergence clones-MDR-HvKPs both highly pathogenic and resistant to most available antibiotics have increasingly been reported. In light of the clonal lineages and molecular characteristics of the studied MDR-HvKP strains in current literature since 2014, this review discusses the epidemiology of MDR-HvKPs, particularly, sums up three general aspects of plasmids-associated mechanisms underlying the formation of MDR-HvKPs clones: MDR-cKPs acquiring hv plasmids, hvKPs obtaining MDR plasmids, and acquisition of hybrid plasmids harboring virulence and resistance determinants. A deeper understanding of epidemiological characteristics and possible formation mechanisms of MDR-HvKPs is sorely needed for the proper surveillance and management of this potential threat.